Glaziale und periglaziale Formbildung in Hoch-Semyen, Nord-Äthiopien - Hastenrath, Stefan (ERDKUNDE, 1974)
Glacial morphology in the peak regions of High Semyen is mapped, and altitudinal zonation of periglacial phenomena is studied in an effort to expand on recent field work in the high mountains of East Africa. Soil frost phenomena are found upwards of 3700 m, with turf exfoliation and micro-terracettes in the vegetation cover occuring between 3780 and more than 4350 m. Above 4250 m, stone stripes, fine earth stripes and polygons are most conspicuous, the characteristic dimension of polygons being considerably smaller than in the East African mountains. In general, observations are spatially consistent with conditions in East Africa. A marked asymmetry in the development of periglaeial forms is noted, with exposures towards the northerly and westerly quadrants being favoured over the southerly and easterly directions. Multiple moraine complexes and cirques are embedded in valleys in the northerly and westerly quadrants of Ras Dadjan, Buahit, and Silki-Abba Yared. Moraines are deeply weathered and carry abundant vegetation. Cirque bottoms lie around 4200-4300 m; lowest moraine ends reach to below 4000 m, and in the massif of Silki-Abba Yared even to about 3750 m. The North-South contrast in glacial and periglacial morphology caused by radiation is peculiar to the outer tropics, and does not occur in equatorial East Africa. The West-East asymmetry results from the powerful diurnal control of circulation systems in low-latitude mountain massifs. This is characterized by a maximum of cloudiness and precipitation in the afternoon, thus reducing the daily totals of insolation on slopes of westerly aspect. From a comparison with the high mountains of East Africa in terms of altitudinal location, soil and vegetation conditions, it is concluded that the moraines in the peak regions of High Semyen were not formed in the course of the last few centuries. In the absence of absolute dating the lowest large moraines can tentatively be correlated with moraine complexes widely occuring on Mts. Kenya and Kilimanjaro with ends around 3400 m (11,000 ft.). The multiple smaller moraines in the upper portion of valleys in High Semyen may have their corollary in similarly arranged moraine arcs around 4000 m on Mts. Kenya (13,000-14,000 ft.) and Kilimanjaro (13,000 ft.). A hypothetical older glaciation in High Semyen extending to below 2600 m may need corroboration in the field; if confirmed, it may have to be viewed in perspective with incomplete indications of older lower-reaching glaciations reported for Mts. Kenya and Kilimanjaro. Other correlations between geomorphic events in High Semyen and the mountains of East Africa appear in context less satisfactory.